Virš žemės = Above the ground - Kurševa, Maija 1981-; Kurševa, Maija 1981-; Lavrinovičs, Andrejs 1987-; Boer, Bas de 1978-; Broeks, Elfie Pop; Frankl-Slater, Camilla 1993-; Kokkonen, Mika; Strautniekas, Karolis 1988-; Valancauskas, Dziugas; Pavilonis, Martynas 1987-; Dubra, Antanas; Egyboy 1982-; et al. (Popper Publishing, 2015)
"Theme of the tenth edition is out of body experiences, intoxication from nature, chemistry, love or heights, psychedelic trips, hallucinations, personal experience and visual side effects." (Verlagsseite)
Pavadošās izstādes: šo izdevumu pavada divas izstādas - Rīga, galerijā "Alma" no 27.03.15 līdz 10.04.15 un Viļnā, galerijā "Malonioji6" no 08.05.15 līdz 20.05.15 = accompanying exhibitions: this edition is accompanied by two exhibitions - in Riga Gallery "Alma" from 27.03.15 till 10.04.15 and in Vilnius Gallery "Malonioji6" from 08.05.15 till 20.05.15
Offsetdruck. - Auflage 500 Exemplare
Keywords: Graphzine